2014
DOI: 10.22302/iccri.jur.pelitaperkebunan.v30i2.4
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Flushing, Cherelle Wilt, and Accuracy of Yield Forecasting of Some Cocoa Clones

Abstract: Monthly observation of cocoa flushing, number of cherelle wilt (CW), number of small, medium and large pods of 6 clones was conducted for two years to study its dynamics for one year. A study was conducted in Kaliwining Experimental Station, 45 m asl. and D rainfall type (according to Schmidt & Ferguson), using ICS 13, ICS 60, TSH 858, Sulawesi 1, Sulawesi 2 and KW 165 clones of 8 years old. Each clone was planted intermittently in separate rows, replicated 6 rows. Correlation and regression analysis were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…On April and September, small pods number (length 2-10 cm), medium pods (length 11-15 cm), large pods (length >15 cm) was observed. The expected yield was calculated by using the opportunities to be harvested as followed 20% of small; 75% of medium; and 95% of large pods (Prawoto, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…On April and September, small pods number (length 2-10 cm), medium pods (length 11-15 cm), large pods (length >15 cm) was observed. The expected yield was calculated by using the opportunities to be harvested as followed 20% of small; 75% of medium; and 95% of large pods (Prawoto, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Citrosupomo (1989) and Pangaribuan (2004) explained that cherelle wilt could reach up to 70-80% from the whole total of formed fruits. Schnappinger et al (2003) and Prawoto (2014) reported that only 32.9% of flowers became harvested pod. Possible concerns to increase the percentage of flowers into pods were pest infestation, cocoa fruit and peel borer, as well as pathogen as cause of diseases such as rotten fruit from the Phytophthora palmivora.…”
Section: Percentage Of Flowers Into Harvested Pod (%)mentioning
confidence: 99%
“…These flowers of cocoa do not contain honey and are odorless, causing difficulties in attracting pollinator insects. In addition, the position of these flowers is facing downwards with its pistiltip higher than the staminode, which gives small chance for pollen to fall onto stigma (Prawoto, 2014).…”
Section: Percentage Of Flowers Into Harvested Pod (%)mentioning
confidence: 99%